(untitled) (REMUNOM, 2024)
Sodium cyclamate is a synthetic sweetener used by the industry in a number of foods, beverages and medicines. The use of this sweetener, generally in the proportion of ten parts of cyclamate to one part of saccharin, results in the enhancement of the sweet taste in addition to masking the bitter taste of saccharin, a synthetic sweetener widely used by the industry in a number of foods, beverages and medicines. In Brazil, until the 1990s, only saccharin, cyclamate and aspartame were used, today the current Brazilian Legislation approves their use in foods, the natural sweeteners sorbitol, mannitol, isomalt, stevioside, maltitol, lactitol and xylitol, and the artificial sweeteners saccharin, cyclamate, aspartame, acesulfame-K and sucralose. Currently, there is great concern about the consumption of products due to excess sodium cyclamate and sweetener levels present. The samples analyzed showed sodium cyclamate levels within the standards established by Brazilian legislation. The sample recovery test demonstrated that the method used to determine cyclamate is reliable.